Performance of allicin coated with palm stearin on hydrolyzation of urea applied on soil. (18th December 2020) - Mathialagan, Ranitha; Mansor, Nurlidia; Shamsuddin, Muhammad Rashid; Noor Affendi, Nur Mahfuzah; Hamid Nour, Abdurahman
Abstract: This paper was focused on the use of allicin as inhibitor which binded with less valuable by-product, palm stearin on urea fertilizer as to increase its efficiency in soil. The coated urea was prepared in three models: urea + palm stearin (UPS), urea + allicin (UAL), urea + allicin + palm stearin (UALPS), whereas pure urea prills act as control (U) sample. The efficiency of the coating materials were investigated through characterization study and this followed by investigation on its N-transformation in soil through quantification of urea-N and ammonium-N remained in soil. Fourier Transformed Infrared Spectroscopy (FTIR) and Thermogravimetric Analysis (TGA) results proved palm stearin as a compatible binder for urea-allicin system as no significant chemical reaction or weight losses occurred compared to control sample, based on their spectrum respectively. Scanning Electron Microscope (SEM) images demonstrated that the micro-structure of UALPS resulted in a smoother coated layer besides hardness test exhibits higher crushing strength. All coated urea fertilizer showed significantly higher nitrogen in urea form (urea-N) in soil compared to control sample. Consequently, nitrogen in ammonium form (ammonium-N) in coated urea fertilizer was lower than uncoated urea as this has proved the coating material has delayed the urea-N release. Besides, UALPS and UAL possess lowest ammonium-N content since the presence of allicin in their coating material had reduced the urease activity in the soil. In overall UALPS, found to be more efficient in reducing the hydrolyzation rate due to the dual effects of material, which may inhibit urease activity and reduce nitrogen (N) releases rate from fertilizer microenvironment.